Perceptions regarding vasopressin use and practices in septic shock, and cost containment strategies. Issue 3 (8th February 2019) - Hammond, Drayton A.; Rech, Megan A.; Daley, Mitchell J.; Devlin, John W.; Hodge, Emily K.; Kooda, Kirstin J.; Lat, Ishaq; Personett, Heather A.; Roberts, Russel; Sacha, Gretchen; Stollings, Joanna L.; Swanson, Joseph M.; et al.
Abstract : Background: Clinician preferences and practices regarding appropriate vasopressin use in light of its increased acquisition cost secondary to rebranding has not been evaluated or described since the most recent iteration of the Surviving Sepsis Campaign Guideline was published. Objective: To assess vasopressin cost containment initiatives and pharmacists' opinions regarding appropriate vasopressin use. Methods: A scenario‐based survey was distributed to critical care and emergency medicine pharmacists. Responses were characterized using frequency and descriptive statistics. Categorical variables between those who implemented changes (Vasopressin Cost Consideration) and those who did not (Usual Care) were compared using chi‐square or Fisher's exact tests. McNemar's test was used to compare responses in clinical scenarios between Vasopressin Cost Consideration and Usual Care groups. Results: Among 1757 pharmacists surveyed, 200 (11.3%) responded. When respondents considered vasopressin cost and evidence (vs evidence alone), fewer respondents would use vasopressin adjunctively with norepinephrine (21% vs 26.6%, P = 0.031), to raise mean arterial pressure compared with epinephrine (65.2% vs 72.3%, P = 0.012), or to reduce norepinephrine infusion rates (71.4% vs 81.4%, P < 0.001), but would use with steroids (62.4% vs 28.3%, P < 0.001). Most (72%) respondents had implemented vasopressin cost containment and/or education initiatives. The Vasopressin Cost Consideration group respondents were more likely to initiate vasopressin at 0.03 units/minute without titrating (47.9% vs 33.9%, P = 0.045). Conclusion: Since vasopressin was generically rebranded, most institutions have implemented at least one initiative to reduce vasopressin use and/or educate clinicians about its appropriate use. When vasopressin acquisition costs were considered, pharmacists recommended its use less frequently, particularly in clinical scenarios where its use is controversial.